Effect of Arnica montana 6 cH on edema, mouth opening and pain in patients submitted to extraction of impacted third molars - Macedo, Sérgio Bruzadelli; Carvalho, J. C T; Ferreira, L. R.; Dos Santos-Pinto, R. [UNESP] (My University, 2005)
This study had the objective to evaluate the homeopathic action of Arnica montana 6 cH and placebo on edema, mouth opening (trismus) and pain in patients submitted to extraction of bilaterally impacted lower third molars. The experiment was carried out as a crossover and double-blind study. The data showed that edema was significantly reduced by the treatment with Arnica montana 6 cH (p<0.05) and did not demonstrate significant effect on trismus and pain as compared to control group.
Keywords: Antiinflammatory; Arnica montana 6 cH; Clinical evaluation; Arnica montana extract; chlorhexidine; felypressin; local anesthetic agent; paracetamol; placebo; povidone iodine; prilocaine; adolescent; adult; antiinflammatory activity; Arnica montana; clinical article; clinical trial; controlled clinical trial; controlled study; crossover procedure; double blind procedure; edema; female; homeopathy; human; male; molar tooth; pain assessment; postoperative infection; postoperative pain; tooth disease; tooth extraction; trismus